2016
DOI: 10.24221/jeap.1.1.2016.1001.96-105
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização anatômica e histoquímica das folhas de Eugenia uniflora L.

Abstract: Eugenia uniflora L., popularmente conhecida como pitangueira, é uma importante frutífera muito utilizada na medicina tradicional brasileira para o tratamento de diarreia e disenteria, gripe, parasitas intestinais, febre, hipertensão e como calmante e diurético. Devido ao seu amplo interesse popular e com o intuito de ampliar as informações farmacobotânicas da espécie, este trabalho tem como objetivo realizar a caracterização anatômica e histoquímica das folhas de E. uniflora. Foram confeccionadas e analisadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…In a study by Cardoso et al (2009), it was observed that 44 Myrtaceae species presented bicolateral vascular bundles, as verified for E. luschnathiana in the present study. This characteristic has also been detected for other species of the genus (DONATO; MORRETES, 2009;DEFAVERI et al, 2011;ESPOSITO-POLESI et al, 2011;SÁ et al, 2016).…”
Section: Qualitative Characteristicssupporting
confidence: 62%
See 3 more Smart Citations
“…In a study by Cardoso et al (2009), it was observed that 44 Myrtaceae species presented bicolateral vascular bundles, as verified for E. luschnathiana in the present study. This characteristic has also been detected for other species of the genus (DONATO; MORRETES, 2009;DEFAVERI et al, 2011;ESPOSITO-POLESI et al, 2011;SÁ et al, 2016).…”
Section: Qualitative Characteristicssupporting
confidence: 62%
“…As for the coating system, some similarities can be observed with studies carried out with other Eugenia L. species such as presence of thick cuticle, hypoestomatic leaf (DEFAVERI et al, 2011;MORRETES, 2009;ESPOSITO-POLESI et al, 2011;DIAS et al, 2012;SÁ et al, 2016), unicellular tectorial trichomes, presence of trichome scars (DEFAVERI et al, 2011;MORRETES, 2009;ESPOSITO-POLESI et al, 2011) and occurrence of epidermal cells of secretory structure surrounded by cells arranged in a radiated form (DEFAVERI et al, 2011;MORRETES, 2009;DIAS et al, 2012;SÁ et al, 2016).…”
Section: Qualitative Characteristicsmentioning
confidence: 52%
See 2 more Smart Citations
“…O formato biconvexo da nervura central também foi encontrado para outras espécies da família Myrtaceae (GOMES et al, 2009;SÁ;SANTANA;RANDAU, 2016). O feixe vascular encontrado apresentou formato bicolateral e um tipo provavelmente novo de feixe concêntrico, pois não foi encontrado tal padrão na literatura.…”
Section: Discussionunclassified